Demographic Determinants of Youth Entrepreneurial Success - Mufaro Dzingirai (IGI Global, 2023)
Youth entrepreneurship has become an interesting phenomenon that has attracted much attention from academics, practitioners, and policymakers across the globe during recent years. The main objective of the paper is to analyze the demographic determinants of youth entrepreneurial success. Employing explanatory research design with a sample of 100 youth entrepreneurs in Gweru who completed the questionnaires, the hypotheses are analyzed using Pearson's correlation and regression analysis in an effort to empirically determine the influence of demographic factors on youth entrepreneurial success. The results show a strong and significant association between entrepreneurial experience and youth entrepreneurial success, a weak positive and significant association between educational qualification and youth entrepreneurial success, a weak negative association between age and youth entrepreneurial success, and a weak negative and significant relationship between gender and youth entrepreneurial success. These outcomes have significant implications for theory, practice, and future research.